Therapeutic targeting of the intestinal barrier in inflammatory bowel disease and graft-versus-host disease - Nalle, Sam (Henry Stewart Talks, 2015)
Comparing/contrasting inflammatory bowel disease (IBD) and graft-versus-host disease (GVHD), Molecular aspects of intestinal epithelial barrier loss in IBD & GVHD, Emerging therapeutic strategies targeting the intestinal barrier in IBD & GVHD